Ketidaksetaraan Ekonomi dan Dampak Sosial Dari Adat Belis Perspektif Akuntansi Budaya di Suku Dawan R, Kabupaten Malaka, Nusa Tenggara Timur (NTT) - Kristina Desy Funan; Ana Sopanah S; Syamsul Bahri; Khojana Hasan (CV. ITTC INDONESIA, 2025)
This study examines the cultural practice of Belis among the Dawan R community in Malaka Regency, East Nusa Tenggara (NTT), from the perspective of cultural accounting, focusing on its economic inequality and social impact. Belis, a customary dowry given by the groom’s family to the bride’s family, holds significant cultural value but often results in economic burdens and social stratification. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation involving traditional leaders, local communities, and government representatives. The findings reveal that while Belis reflects local wisdom and strengthens family ties, it also contributes to financial hardship, reinforces gender inequality, and leads to various social issues such as labor exploitation, debt, early marriage, and domestic violence. From a cultural accounting perspective, Belis can be analyzed through the stages of identification, measurement, and communication, representing a form of economic transaction rooted in local tradition. This research recommends policy reform and community education to harmonize cultural preservation with economic and social justice, including setting reasonable limits on Belis, promoting non-monetary alternatives, and increasing economic literacy.